Masalah Kemanusiaan hingga Lingkungan Hidup: Studi Kasus Konflik Nagorno-Karabakh (Azerbaijan Vs Armenia) - Arinawati, Hanna; Putri, Fathimah Azzahrah; Islamy, Shereena El (Faculty of Law, Universitas Jambi, 2021)
Armed conflict in a war is recognized as one way to resolve disputes between countries. However, armed conflict has negative impacts on humanity and the environment. This study discusses the conflict between Azerbaijan and Armenia which resulted in the deaths of 150 civilians and 5000 soldiers died and had a negative impact on the environment. Azerbaijan was accused that in this war it used White Phosphorus or fireworks with white smoke which carries a very dangerous chemical, it can cause disability or the extinction of wildlife forever. Meanwhile, the Armenians exploited the natural resources of the occupied territories without considering the superiority of population interests and changes in regional cultural heritage. The results showed that in the Nagorno-Karabakh conflict 2020 (Azerbaijan vs. Armenia) there were violations of international agreements in international environmental law and international humanitarian law that occurred as a result of the conflict which could be held accountable internationally. Then in relation to accountability due to armed conflict, Armenia and its affiliates in the occupied territory of Azerbaijan are responsible for acts of international violations